Floricoccus tropicus gen. nov., sp. nov. and Floricoccus penangensis sp. nov. isolated from fresh flowers of durian tree and hibiscus - Chuah, L.O.; Yap, K.P.; Ahamed Kamal, S.S.; Thong, Kwai Lin; Ahmad, R.; Liong, M.T.; Rusul, G. (Society for General Microbiology, 2017)

(untitled)
Three strains of Gram-staining-positive, coccus-shaped, lactic acid bacteria, designated as HibF3T, HibF2 and HibF5 were isolated from fresh flowers of hibiscus, and a fourth, DF1T, was isolated from fresh flowers of durian tree, in Penang, Malaysia. Taxonomic characterisation was performed by polyphasic analysis. Sequence similarities of the 16S rRNA gene and the housekeeping rpoA and pheS genes of these strains with their closely-related lactococcal and streptococcal relatives were 92–94, 78 and 81 %, respectively. The results of phylogenetic analysis indicated that strains DF1T, HibF2, HibF5 and HibF3T were clustered together but were clearly separated from species of the genera Streptococcus and Lactococcus, indicating that they represent members of a novel genus of the family Streptococcaceae. Calculation of average nucleotide identity (ANI) values between the genomes of DF1T and HibF3T yielded values of 92.50–92.93 %. ANI values below the cut-off value and distinctive chemotaxonomic characteristics supported the hypothesis that these strains represented two novel species. Major cellular fatty acids in DF1T, HibF2 and HibF5 were C18 : 1!7c and C16 : 0, while C12 : 0 and C14 : 0 were also dominant, in addition to C18 : 1!7c and C16 : 0, in HibF3T . A novel genus is proposed with the name Floricoccus gen. nov. which consists of two species, Floricoccus tropicus sp. nov as the type species, and Floricoccus penangensis sp. nov. The respective type strains are DF1T(=LMG 29833T=JCM 31733T) and HibF3T (=LMG 29831T=DSM 31735T).